MHD Falkner-Skan Flow with Mixed Convection and Convective Boundary Conditions - KHAN, Masood; ALI, Ramzan; SHAHZAD, Azeem (Walailak Journal of Science and Technology (WJST), 2013)
In this paper we investigate the simultaneous effects of thermal and concentration diffusions on a mixed convection magnetohydrodynamic (MHD) Falkner-Skan boundary layer flow through a porous medium under a convective surface boundary condition. The governing boundary layer equations are written in dimensionless form by similarity transformations. The transformed coupled nonlinear ordinary differential equations are solved analytically by using the homotopy analysis method (HAM). The effects of different parameters on the velocity, temperature and concentration fields are analyzed and discussed. Tables containing the numerical data for the local Nusselt and Sherwood numbers are also provided.